Analysis of Power Distance and Its Consequences in Affiliated Hospitals of Tehran University of Medical Sciences - S Rafeiyee; A Pour reza; A Rahimi (Tehran University of Medical Sciences, 2014)
Abstract Background: Human resource management has a critical role in organizations and organization culture is an outcome of human resource management performance. One of the dimensions of the organizational culture is power distance. This study aims to investigate the attitude of employees of selected hospitals of Tehran University of medical sciences towards the power distance in the organization and its consequences. Materials and Method: This is a cross sectional study with a descriptive research design conducted in a sample of 306 employees and managers from Tehran University of Medical Sciences hospitals located in Tehran, Iran. A distinctive questionnaire for each group was developed, distributed and collected as a main procedure to gather data. Data were analyzed using SPSS 16. Results: Study results indicates that there is a positive and significant relationship between power distance and employee participation, organizational commitment, job satisfaction, perception of justice and readiness to accept job responsibilities in the level of 95%(p value<0.05). The moderated multiple regression results also supported the hypothesis that managers' attitude towards power distance had a significant relationship with their manner with the employees, noticing their qualifications and abilities, giving them independence and responsibility and supporting them in their role. Conclusion: A limited power distance in an organization will result in more committed and satisfied employees with positive perception toward justice in the organizational interactions and ready to accept job responsibilities and movement toward the organization objectives.